P. Allen Smith's container gardens : 60 container recipes to accent your garden - Smith, P. Allen (Clarkson Potter, 2005)
Presents a detailed guide to the art of container gardening, with instructions presented in a recipe format for creating unique containers designed to enhance the beauty of a home garden.